Peningkatan Kapabilitas Kewirausahaan Pinggiran: Pelatihan Digital Marketing untuk Wirausahawan HIDIMu - Hananto, Mursid Wahyu; Setyono, Hendro; Nour, Azty Acbarrifha (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Marginal entrepreneurship refers to entrepreneurs who have structural and cultural barriers in utilizing access to maintain and develop their businesses. Barriers arise due to various factors such as gender bias, or having a disability. Entrepreneurs with disabilities have difficulty maintaining the sustainability of their businesses or developing them because physical limitations make it difficult to market their products or services. The community service team of Universitas Ahmad Dahlan (UAD) held a series of digital marketing trainings funded by the Ministry of Education, Culture, Research and Technology's DRTPM for entrepreneurs with disabilities who are members of the Muhammadiyah Disability Association (HIDIMu). The service aims to provide the ability for entrepreneurs with disabilities to independently expand their marketing reach so that they can get more potential consumers for their business activities. The service is carried out with stages of socialization, training, implementation, and mentoring. The results of the service activities show that entrepreneurs who previously relied on physical marketing now have the ability to market products digitally using various technologies and innovations from various online media. This ability reduces physical work and time to promote their businesses so that efficiency is achieved. Evaluation of the results of the community service showed an increase in understanding of marketing by 48%; management by 28%; digital marketing techniques by 56%; ability to apply digital marketing for entrepreneurial activities by 70%; and marketing reach by 89%. Overall, the community service activities have succeeded in increasing the entrepreneurial capabilities of HIDIMu members. The marketing reach extends beyond provincial boundaries, so that it can reach more potential consumers to increase the opportunity for transactions.